2011
DOI: 10.1007/s11884-011-0081-z
|View full text |Cite
|
Sign up to set email alerts
|

Purinoceptors and Bladder Dysfunction

Abstract: Purinergic signaling is increasingly appreciated as an important contributor to the normal bladder functions of urine storage and voiding. The translation of disease and injury to abnormal sensory and motor function, resulting in lower urinary tract symptoms, is in part mediated by the interaction of adenosine 5′-triphosphate and related purines with specific purinergic receptors (purinoceptors). Identification and clarification of purinoceptor-based processes are important research goals aimed at novel therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Purinergic signaling is increasingly appreciated as an important contributor to the normal bladder functions of urine storage and voiding. e translation of disease and injury to abnormal sensory and motor function, resulting in lower urinary tract symptoms, is in part mediated by the interaction of adenosine 5′-triphosphate and related purines with specific purinergic receptors [17]. Evidence-Based Complementary and Alternative Medicine e role of purinergic signaling in the regulation of urinary bladder function was established when published reports demonstrated that P2X 2 /P2X 3 knockout animals had significantly altered bladder function.…”
Section: Discussionmentioning
confidence: 99%
“…Purinergic signaling is increasingly appreciated as an important contributor to the normal bladder functions of urine storage and voiding. e translation of disease and injury to abnormal sensory and motor function, resulting in lower urinary tract symptoms, is in part mediated by the interaction of adenosine 5′-triphosphate and related purines with specific purinergic receptors [17]. Evidence-Based Complementary and Alternative Medicine e role of purinergic signaling in the regulation of urinary bladder function was established when published reports demonstrated that P2X 2 /P2X 3 knockout animals had significantly altered bladder function.…”
Section: Discussionmentioning
confidence: 99%